Socialization, Tacit Knowledge, and Conceptions of 'Experience' among Engineers. Issue 1 (2nd January 2022) - Wylie, Caitlin D.; Kim, Suk Jun
Abstract : Engineers value undergraduate research experience as an important step towards becoming an engineer. However, what the word 'experience' means in this context is ambiguous. We draw from qualitative interviews with engineering faculty members, graduate students, and undergraduate students to identify four categories of experience that they consider relevant to engineering: (1) practical experience: 'real-world' skills and opportunities that resemble the work done in engineering careers and graduate school, (2) social experience: the interpersonal aspects of working with a team, including norms of behavior and communication, (3) professional experience: skills and opportunities that are useful in aspects of students' lives beyond a specific job, such as how to manage their time, and (4) epistemic experience: learning about and applying abstract engineering knowledge. By deriving a typology of 'experience' based on how faculty members and students talk about undergraduate research, this study offers insights into how engineers in universities understand engineering expertise, professionalization, and collaboration. Reflecting on what kinds of 'experience' a good engineer needs also reveals the power dynamics between mentors and novices, and between junior engineers' sometimes conflicting roles as both laborers and learners.